Implementasi Strategi Quick on the Draw dalam Pembelajaran Memahami Informasi Teks Deskripsi: Implementation of Quick on the Draw Strategy in Learning to Understand Description Text Information - Intama Jemy Polii; Abdul Muqit; Justien R. R. Wuisang; Jerry Rommy Herter Wuisang (Society, 2021)
This classroom action research aimed to improve the seventh-grade students of SMP Negeri 4 Tondano (Public Middle School) in understanding the information of a descriptive text. This research was conducted in two cycles. The research subjects were 28 students of class VII-A. The results showed that implementing the Quick on the Draw strategy in learning to understand descriptive text information created a learning atmosphere that excites students. It allows all students to play active roles during the learning as the nine steps of Quick on the Draw place students as the subject. Students use their potentials to think independently, solve problems jointly, and obtain additional information not provided by the teachers. The final test results showed that from 28 students, 27 students (96.42%) scored above 75, and 1 student (3.58%) below the standard. The ability of students to understand classical descriptive text information was 83, beyond the Minimum Learning Mastery Standard.